PEDAGOGICAL AND PSYCHOLOGICAL OPPORTUNITIES OF USING ARTIFICIAL INTELLIGENCE TOOLS IN INDEPENDENT ENGLISH LANGUAGE LEARNING (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The rapid development of artificial intelligence (AI) technologies has significantly transformed language learning paradigms, particularly in the context of independent learning. This study explores the pedagogical and psychological opportunities offered by AI-based tools in the process of autonomous English language acquisition. The research adopts a qualitative-analytical approach, examining current AI applications such as intelligent tutoring systems, chatbots, and adaptive learning platforms. Findings indicate that AI enhances learner autonomy, provides personalized feedback, and supports motivation through interactive engagement. Psychologically, AI tools contribute to reducing anxiety, increasing self-efficacy, and fostering continuous learning habits. The paper concludes that integrating AI into independent language learning environments can significantly improve learning outcomes when aligned with pedagogical principles.